A primer for financial engineering : financial signal processing and electronic trading - Akansu, Ali N., 1958-; Torun, Mustafa U. (Academic Press, 2015)
This book bridges the fields of finance, mathematical finance and engineering, and is suitable for engineers and computer scientists who are looking to apply engineering principles to financial markets.